Risk factors of bronchiolitis - I Gde Doddy Kurnia Indrawan; IB Subanada; Rina Triasih (Indonesian Pediatric Society, 2013)
Background Bronchiolitis peak incidence is in children aged 2 -6months. History of atopy in parents, non-exclusive breastfeeding,exposure to cigarette smoke, and infants living in crowded areasmay be risk factors for bronchiolitis. Gestational of age at birth isalso influences the mortality oflower respiratory tract infection.Objective To evaluate the following conditions as possiblerisk factors for bronchiolitis: history of atopy, non-exclusivebreastfeeding, preterm infants, exposure to cigarette smoke, and2:: 6 persons residing in the home.Methods A sex-matched case-control study was conductedby collecting data from medical records at Sanglah Hospital,Denpasar. The case group subjects met the diagnostic criteriafor bronchiolitis and were aged 1-24 months. The control groupincluded patients with diagnoses unrelated to the respiratorysystem. Data was analyzed using bivariate (Mc.N emar) andmultivariate methods (logistic regression) with 95% confidenceintervals and statistical significance value of P <0 .05.Results There were 96 subjects in our study, consisted of 48subjects in the case group and 48 in the control group. Thecase and control groups were similar in baseline characteristics.The presence of history of atopy (OR 34.7; 95%CI 3 to 367,P=0.003), non-exclusive breastfeeding (OR 4.3; 95%CI 1.4 to13, P=0.010), exposure to cigarette smoke (OR 3; 95%CI 1 to9.2, P=0.047), and 2:: 6 persons living in the home (OR 7.9;95%CI 2.6 to 24, P<0.0001) were found to be significant riskfactors for bronchiolitis, while the preterm infants seem notsignificant as a risk factor of bronchiolitis (OR3; 95%CI 0.31 to78.99, P=0.625).Conclusion History of atopy, non-exclusive breastfeeding,exposure to cigarette smoke, and 2:: 6 persons living in the homeare found to be risk factors, while preterm infants seem not a riskfactor for bronchiolitis.